Lives stalled: the costs of waiting for refugee resettlement. Issue 11 (18th August 2022) - Fee, Molly
ABSTRACT: During their migration, refugees often pass through transit countries, especially before resettlement elsewhere. These stays in cities or camps may last several months or years as refugees await the next step of their journey. This paper examines the context of waiting for Iranian religious minorities who must first travel to Vienna, Austria in order to apply for resettlement to the U.S. Drawing on theories of waiting, I demonstrate how uncertainty and the passage of time shape refugees' experience in transit contexts. While in Vienna, they endure months of compulsory idle waiting, free from persecution yet unable to begin the long-term process of settling in a new country. I argue that the duration of stay and conditions of life in transit contexts can have meaningful consequences for refugees. My findings demonstrate that even when waiting is temporary and remedied by eventual resettlement, time spent in transit carries material, emotional, and physical costs. Based on 43 interviews and participant observation with Iranian refugees in Vienna, this paper examines the precarity that is born from the uncertainty of waiting. Because resettlement ultimately provides stability, we tend to overlook the insecurities associated with this 'pre-resettlement' phase.